MEDIA SOSIAL MENDONGKRAK EKONOMI LOKAL PEKON SUMBER MULYO - Anita, Anita; Mufahamah, Euis; Listyaningsih, Erna; Sagala, Raihan Zaky; Dafitri, Rizkika (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2024)
The economic activity in rural areas is increasingly rapid. The need for development to expand market share. Through social media which is a driving factor as part of technological progress, it needs to be utilized as well as possible by the community. Not only can it be used as a means of entertainment, but it can also be used as a marketing medium. The advancement of social media can bring about major changes in the way we communicate, interact, and participate in digital culture. Social media can be a positive force in advancing Indonesian society in the future if we can monitor it carefully and manage it wisely. In addition, the benefits of social media for business development are that social media can help businesses such as promoting products and brands, so that products can be known by more people. Pekon Sumber Mulyo has a lot of economic potential, so intermediaries are needed to market its local products. Education in this service is expected to have a broad impact, especially on the young men and women of Karang Taruna Pekon Sumber Mulyo who are mostly social media users in order to boost their local economy.